The impacts of natural and anthropogenic factors on vegetation change in the Yellow-Huai-Hai River Basin - Wu, Houfa; Zhang, Jianyun; Bao, Zhenxin; Wang, Guoqing; Wang, Wensheng; Yang, Yanqing; Wang, Jie; Kan, Guangyuan (Frontiers in Earth Science, 2022)
The Yellow-Huai-Hai River Basin (YHHRB) is an important ecological barrier in China. There are obvious spatiotemporal differences and intrinsic drivers of vegetation coverage in this region. Using the Normalized Difference Vegetation Index (NDVI) and meteorological data, the spatiotemporal characteristics of vegetation change in the YHHRB from 1982 to 2015 and its related driving factors were analyzed. Combined with CAM5.1-1degree model data, the impacts of natural and anthropogenic forcings on climate change were separated, and the relative roles of other driving factors, natural and anthropogenic forcings in vegetation change were further distinguished by using a residual trend method. Results showed that the vegetation coverage increased during the study period, the NDVI increased with a slope of 0.014/10a, and the areas with NDVI significant increased accounted for 75.78%. NDVI was positively correlated with precipitation and temperature in the YHHRB, and the correlation between NDVI and temperature was higher than that of precipitation, indicating that vegetation growth was more sensitive to temperature. Residual analysis indicated that other driving factors, natural and anthropogenic forcings were responsible for 48.52%, 26.36% and 25.12% of NDVI variation, respectively. Natural forcing contributed most to vegetation change in the Huai River Basin, whereas anthropogenic forcing and other driving factors had large effects on vegetation coverage in the Hai River Basin. In addition, obvious spatial differences were observed in the relative roles of different driving forces on vegetation condition. The areas where natural forcing contributed most were mainly distributed in the upper Yellow River Basin, while the areas where other driving factors played a significant role in vegetation restoration were mainly concentrated in Inner Mongolia, Shanxi Province and northern Hebei Province. Climate change and active human activities both made positive impacts on vegetation restoration, and the change of landuse was the main factor causing vegetation degradation. The results provide a theoretical basis for the ongoing ecological civilization construction project in the YHHRB.